(untitled) (Global Journal of Science Frontier Research, 2023)
Saliva has been studied extensively as a potential diagnostic tool over the last decade due to its ease and noninvasive accessibility along with its abundance of biomarkers such as genetic material and proteins The activity of protein in saliva increased during ovulation When we monitored salivary protein activity in 40 different women volunteers during various stages of reproduction like prepubertal parous non-parous menopausal and in the metabolic disorder state diabetic condition it has been observed that highly significant p 0 001 increase in parous ovulatory non parous ovulatory whereas highly significant p 0 01 increase was observed in non-parous postovulatory and a highly significant p 0 001 decrease was observed in menopause and diabetic in comparison to prepubertal A highly significant p 0 001 decrease was observed in menopause in comparison to parous preovulatory ovulatory post ovulatory non-parous ovulatory and postovulatory A highly significant p 0 01 decrease was observed in diabetic in comparison to menopausal human female subjects The result revealed that the total protein was considered as testing the saliva instead of blood isa non-invasive loom and it can be used as a biomarker for ovulation detection